Calidad de vida en cuidadores de niños y niñas con enfermedades raras (2019)
This is a non experimental quantitative study, with a descriptive scope, with a cut off in the first semester of the year 2019, 96 Family Caregivers from the FUPER Foundation from the city of Medellin, Colombia, participated. The instruments were used Characterization sheet of the dyad Carer-person with chronic disease GCPC-UN-D1 and Quality of Life Instrument Family Carer Version Quality of Life version. (QOL) The analysis was carried out using descriptive statistics, the nonparametric Kolmogórov-Smirnov test and the determination of the Spearman correlation coefficient using the IBM SPSS Version 25 program